Investigation on increment and wood production of Cupressus sempervirens L. var. horizontalis in Kordkuy plantation forest - Adrdalan Ahmadi; Asghar Fallah (تحقیقات جنگل و صنوبر ایران, 2009)
This study was conducted to determine the increment and wood production of 22-year-old cypress plantation in Kordkuy region in the north of Iran. Thirty sample plots, each 200m2 area were selected at 101 ha of Cypress man-made forest which was planted in 2mÍ2m spacing. The samples were taken by systematic random method. In each sample plot, diameter at breast height (DBH) of whole trees and height of witness trees were measured. Moreover, 53 trees were selected as sample trees based on classified diameter in sample plots and felled trees. The data were analyzed with SPSS and Excel softwares. Results showed that the survival rate was 58.72%. The quantitative parameters were calculated and revealed that mean DBH, mean height, basal area, volume and annual volume increment were 15.2cm, 14.02m, 24.35cm2 ha-1, 157.31 silve and 7.15 silve ha-1 y-1, respectively. Results showed the studied plantation compare to Cypress plantations in other parts of the country is promising